2011
DOI: 10.1016/j.cvsm.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Canine Coronavirus: Not Only an Enteric Pathogen

Abstract: This article reviews the currently available literature on pantropic canine coronavirus (CCoV), providing a meaningful update on the virologic, epidemiologic, clinical, diagnostic, and prophylactic aspects of the infections caused by this emerging pathogen of dogs. It also describes pantropic CCoV-induced disease reproduced under experimental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 45 publications
1
76
0
4
Order By: Relevance
“…Although our prevalence data are poorly informative about the impact of infection and disease in the populations, previous studies have shown that CCoV infection seems not to be frequently associated with fatal disease; instead, it often causes mild, self-limiting enteritis followed by rapid recovery [47]. Nevertheless, mortality may occur as a consequence of mixed infections with any of the two studied virus, CPV and/ or CDV [47,48].…”
Section: Canine Coronavirusmentioning
confidence: 87%
“…Although our prevalence data are poorly informative about the impact of infection and disease in the populations, previous studies have shown that CCoV infection seems not to be frequently associated with fatal disease; instead, it often causes mild, self-limiting enteritis followed by rapid recovery [47]. Nevertheless, mortality may occur as a consequence of mixed infections with any of the two studied virus, CPV and/ or CDV [47,48].…”
Section: Canine Coronavirusmentioning
confidence: 87%
“…Canine viral enteritis is a major cause of death among dogs of very young age. The leading causes of canine viral enteritis include canine parvovirus 2, canine coronavirus and rotaviruses (Decaro and Buonavoglia, 2011;Osterhaus et al, 1980). More recent studies also attribute a role to caliciviruses and astroviruses (Castro et al, 2013;Martella et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Fatal disease may occur as a consequence of mixed infections with CCoV together with CPV-2, Canine adenovirus type 1, or Canine distemper virus. 2,3 However, a hypervirulent variant, named pantropic CCoV, has been reported to cause fatal disease in infected dogs. 1,6,14 Canine coronavirus is an enveloped, singlestranded, positive-sense RNA virus belonging to the genus Alphacoronavirus (family Coronaviridae, subfamily Coronavirinae), species Alphacoronavirus 1, which also includes Feline coronavirus, Transmissible gastroenteritis virus (TGEV) of swine, and its derivative, Porcine respiratory coronavirus.…”
Section: 9mentioning
confidence: 99%
“…To date, 2 different genotypes of CCoV are known, I (CCoV-I) and II (CCoV-II). 2,3 Canine coronavirus type II is divided into 2 subtypes, IIa (classical strains) and IIb, with CCoV-IIb emerging as a result of a putative recombination between CCoV-IIa and TGEV. 13 Several studies have assessed the CPV and/or CCoV type distribution in different European countries, [6][7][8]13,18,20,21 but, to date, there is no epidemiological data about the circulation of these enteric pathogens in Albania.…”
Section: 9mentioning
confidence: 99%